2014
DOI: 10.1007/s11033-014-3501-2
|View full text |Cite
|
Sign up to set email alerts
|

NDRG1 expression is related to the progression and prognosis of gastric cancer patients through modulating proliferation, invasion and cell cycle of gastric cancer cells

Abstract: N-myc downstream-regulated gene 1 (NDRG1) has been proposed as a tumor suppressor gene in many different types of tumors, but its potential function and corresponding mechanism are not yet fully elucidated. This study aims to detect the possible function of NDRG1 in gastric cancer progression. In this study, 112 paired gastric cancer tissues and corresponding nonmalignant gastric tissues were utilized to identify the differential protein expression of NDRG1 by immunohistochemistry and its clinical significance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 34 publications
4
42
1
Order By: Relevance
“…N-myc downstream-regulated genes (NDRGs) represent a family of proteins with unknown function. NDRG1 is a metastasis suppressor relevant for cancer progression and prognosis (Chang et al., 2014), its exact molecular function has remained unknown. RBDmap resolves a conserved RNA-binding region within the NDR domain of NDRG1, NDRG2, and NDRG4.…”
Section: Resultsmentioning
confidence: 99%
“…N-myc downstream-regulated genes (NDRGs) represent a family of proteins with unknown function. NDRG1 is a metastasis suppressor relevant for cancer progression and prognosis (Chang et al., 2014), its exact molecular function has remained unknown. RBDmap resolves a conserved RNA-binding region within the NDR domain of NDRG1, NDRG2, and NDRG4.…”
Section: Resultsmentioning
confidence: 99%
“…NDRG1 has been found to either promote or inhibit the proliferation of different cancer cells [10][13][26]. To investigate the potential role of NDRG1 in the development of NPC, we used shRNA to knock down NDRG1 in 5–8F cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that NDRG1 plays different roles in different types of tumors. NDRG1 appears to serve as a putative tumor suppressor and is down-regulated in colorectal [11,12], gastric [13], cervical [14], ovarian [15] and prostate [16] cancers.…”
Section: Introductionmentioning
confidence: 99%
“…The intensity score represented the estimated staining intensity as follows: 0, no or marginal staining; 1, weak; 2, moderate; 3, intense. The total score ranged from 0-12, with 0 representing negative, 1-4 representing weak positive, 6-8 indicating moderate positive and 9-12 describing an intense positive score (19,20).…”
Section: Methodsmentioning
confidence: 99%